Comparison of Manual Small Incision Cataract Surgery between the Patients of Cataract with Pseudoexfoliation and Those without Pseudoexfoliation: Doi: 10.36351/pjo.v37i4.1297 - Yadav, Priyanka; Goyal, Yashas; Dewan, Lubhavni; Nema, Nitin (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare the risk factors, intraoperative complications and postoperative visual outcome between patients of cataract with pseudoexfoliation (PXF) and those without pseudoexfoliation undergoing manual small incision cataract surgery (MSICS) with posterior chamber intra ocular lens implantation. Study Design: Quasi experimental study. Place and Duration of Study: Methods: Fifty-six eyes of patients with cataract and PXF and 56 eyes of patients with cataract without PXF were recruited. Complete history and ocular examination was performed. Pre-operative pupillary dilation of the eye to be operated was measured. Manual small incision cataract surgery was performed with implantation of posterior chamber intraocular lens. Patients were examined on 1st post-operative day then on45th day. Risk factors for per-operative complications and visual outcomes were compared between two groups. Results: Mean age in the PXF group was 55 ± 5 years and in the control group was 45 ± 5 years. PXF group showed female preponderance. Preoperative risk factors (higher in the PXF group) included poor pupillary dilatation, iridodonesis, zonular weakness/phacodonesis and subluxation. PXF was associated with raised intraocular pressure (10.6%). In 5% cases of PXF, intraoperative posterior capsular rent and vitreous loss occurred. Best-corrected visual acuity on the 45th postoperative day was significantly better in patients without PXF (p-value < 0.05). Conclusion: Cataract patients with PXF have higher preoperative risk factors for intra-operative complications as compared to patients without PXF. This can result in compromised visual outcome as compared to the eyes without PXF. Key Words: Cataract, Pseudoexfoliation, manual small incision cataract surgery, iridodonesis, phacodonesis.